Brothers at bat : the true story of an amazing all-brother baseball team - Vernick, Audrey; Salerno, Steven (New York : Clarion Books, 2012)
Documents the story of the Baseball Hall of Fame honorees, tracing how the Acerra family of New Jersey formed their own semi-pro baseball team in the 1930s and became the longest-running all-brother team in history.
AD 780
Keywords: Acerras (Baseball team); Baseball teams -- United States -- History; Brothers -- Biography; Baseball teams -- New Jersey -- History